2006
DOI: 10.1300/j027v24n04_01
|View full text |Cite
|
Sign up to set email alerts
|

Routine PHQ-9 Depression Screening in Home Health Care: Depression Prevalence, Clinical and Treatment Characteristics, and Screening Implementation

Abstract: This study aimed to examine: the prevalence and correlates of depression among adults age 65 and over on admission to diverse home health care programs; nurse compliance with routine screening using the PHQ-9; and concordance between the number of depressed individuals identified by the PHQ-9 and Medicare-mandated nursing assessment following targeted nurse training in identifying depression among the elderly using a standard diagnostic screen. Data are drawn from routine screening of 9,178 patients (a 77% scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 46 publications
6
103
3
Order By: Relevance
“…In this study, 12.5% of clients had significant symptoms of depression, which is similar to the prevalence rates reported in other Canadian (Victorino et al, 2003) and American (Bruce et al, 2002;Ell et al, 2005) studies. A DRS score of 3 or higher is intended to serve as an alert for the presence of depression and to aid in decisions relating to care planning and service provision.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 12.5% of clients had significant symptoms of depression, which is similar to the prevalence rates reported in other Canadian (Victorino et al, 2003) and American (Bruce et al, 2002;Ell et al, 2005) studies. A DRS score of 3 or higher is intended to serve as an alert for the presence of depression and to aid in decisions relating to care planning and service provision.…”
Section: Discussionsupporting
confidence: 91%
“…(2001), and has since been used widely to screen for depressive symptoms. This scale is relatively easy to administer as well; prior research has demonstrated its reliability in primary care settings when administered by non-psychiatric interviewers (Ell et al ., 2006). Because Korean older adults tend to complain about somatic symptoms rather than cognitive and emotional ones (Lee and Farran, 2004), we determined that the PHQ-9K would be well suited to our study.…”
Section: Depressionmentioning
confidence: 99%
“…A study using the PHQ-9 to determine probable major and minor depression in 930 newly admitted home care program participants found that older adults who were female and Latino were more likely to score in the probable minor or major depression range, and those who were married and African American were less likely to score in this range (Ell et al, 2005). Another study found no difference in rates of depression between 56 African American and 458 White older adult newly admitted home health care recipients as determined by the Structured Clinical Interview for DSM-IV disorders (SCID; Fyffe, Sirey, Heo, & Bruce, 2004).…”
Section: Depression Risk Factorsmentioning
confidence: 99%
“…Research shows that home health care nurses can be trained to better identify depression in their routine provision of care Brown et al, 2010;Bruce et al, 2007). Studies find that the PHQ-9 is more accurate at identifying depression than the PHQ-2 used in the OASIS (Ell et al, 2005); however, training in better use of the OASIS may also be acceptable. One intervention developed for this purpose is the TRaining In the Assessment of Depression (TRIAD) intervention, which helped home care nurses use the OASIS screening to more accurately identify depression Brown et al, 2010;Bruce et al, 2007).…”
Section: Delivery System Designmentioning
confidence: 99%
See 1 more Smart Citation